Temperature Dependence of the Enhancement of a7 Nicotinic Receptor Activity by Potential Therapeutic Compounds - Nielsen, Beatriz Elizabeth (2015)
Alpha 7 nicotinic acetylcholine receptors (nAChRs) are widely distributed throughout the central nervous system, mainly in hippocampus and cortex, and are implicated in several neurological disorders such as Alzheimer´s disease and schizophrenia. Enhancement of α7 nAChR activity by positive allosteric modulators (PAMs) is a promising therapeutic strategy to improve cognitive deficits. PAM activity has been evaluated mainly at the macroscopic level, and PAMs have been classified as type I, which increase α7 currents, and type II, which cause also a profound decrease in desensitization and/or reactivate desensitized receptors. In addition, most in vitro studies have been performed at room temperature whereas preclinical studies and clinical use require physiological temperatures. To cover these limitations we evaluated potentiation of human α7 at the single-channel level. Our results revealed that both types of PAMs enhance open-channel lifetime and produce activation episodes of successive opening events. By analyzing their activities at a physiological temperature, we found that potentiation decreases with respect to room temperature. However, both PAM types show different sensitivity to temperature, suggesting distinct mechanisms by which they induce sustained activation. Overall, temperature dependence analysis emerges as a key requisite during evaluation of potential clinical applications of PAMs.